On Sπ Weakly Regular Rings, II - Shahla Khalil (Al-Rafidain Journal of Computer Sciences and Mathematics)
The main purpose of this paper is to study right(left) Weakly regular rings. also we give some properties of Weakly regular rings, and the connection between such rings and CS-rings, MGP-rings and SSGP-rings.